2020
DOI: 10.1016/j.dcn.2020.100810
|View full text |Cite
|
Sign up to set email alerts
|

The rhythm of learning: Theta oscillations as an index of active learning in infancy

Abstract: Highlights A novel, cutting-edge measure for studying active learning in infancy is introduced: theta oscillations. Theta rhythms are linked to expectation of information, memory, and reward processing, making it an ideal candidate for studying active learning. Existing evidence and potential applications of theta oscillations in research on infant active learning are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 86 publications
10
73
1
Order By: Relevance
“…Theta rhythm in infancy is an indicator of active learning and memory (Begus & Bonawitz, 2020). Studies have shown that the connection between theta power recorded in the cerebral cortex and new information coding (Klimesch et al., 2008) is caused by cortical theta activity induced by cortical hippocampal feedback circuit, and theta rhythm (Lega et al., 2012) may also induce synaptic plasticity (Begus & Bonawitz, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theta rhythm in infancy is an indicator of active learning and memory (Begus & Bonawitz, 2020). Studies have shown that the connection between theta power recorded in the cerebral cortex and new information coding (Klimesch et al., 2008) is caused by cortical theta activity induced by cortical hippocampal feedback circuit, and theta rhythm (Lega et al., 2012) may also induce synaptic plasticity (Begus & Bonawitz, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Theta rhythm in infancy is an indicator of active learning and memory (Begus & Bonawitz, 2020). Studies have shown that the connection between theta power recorded in the cerebral cortex and new information coding (Klimesch et al., 2008) is caused by cortical theta activity induced by cortical hippocampal feedback circuit, and theta rhythm (Lega et al., 2012) may also induce synaptic plasticity (Begus & Bonawitz, 2020). In HIE term infants with selective neuronal damage, the cerebral cortical and hippocampal neurons are most vulnerable to damage, so the communication between the theta band cortex and hippocampus is blocked (Lega et al., 2012), which affects infants’ cognitive function such as memory and learning.…”
Section: Discussionmentioning
confidence: 99%
“…In the brain of human adults, the theta rhythm has long been associated with the processing of prediction errors (Cavanagh et al, 2010), cognitive conflict (Hanslmayr et al, 2008), and mnemonic control (Friese et al, 2013; Köster et al, 2018). Furthermore, the theta rhythm has been associated with learning processes in children (Köster et al, 2017), and infants (Begus et al, 2015; Begus and Bonawitz, 2020). Our findings highlight that the theta rhythm promotes the processing of novel, unexpected information, in the sense of prediction errors, already in early infancy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, infants’ neural oscillatory dynamics were rhythmically entrained at 4 Hz or 6 Hz, and the presentation of unexpected events led to a specific increase in the entrained 4 Hz but not in the 6 Hz activity (Köster et al, 2019). Critically, 4 Hz oscillatory activity corresponds to the neural theta rhythm, a frequency which plays an essential role in prediction error processing in adults (Cavanagh and Frank, 2014) as well as learning processes in adults (Friese et al, 2013; Köster et al, 2018), children (Köster et al, 2017), and infants (Begus et al, 2015; Begus and Bonawitz, 2020). However, it has not been investigated how the ongoing oscillatory activity (i.e., not entrained or tightly locked to the stimulus onset) responds to unexpected events in the infant brain and, specifically, whether the ongoing theta rhythm marks infants’ processing of prediction errors.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation